Pengaruh Kebermanfaatan, Kemudahan, Keamanan, Serta Kepuasan Pengguna Dan Kesiapan Teknologi Informasi Terhadap Penggunaan E-Filing Pada Wajib Pajak Polri - Indira Puspasari; Baihaqi Baihaqi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
E-Filing is a way of submitting tax returns and submitting renewal notices for both periodic and annual tax returns electronically which are carried out online and in real time through an Application Service Provider (ASP). This study aims to determine the factors that influence the use of e-filing for police taxpayers. The variables used in this study are the dependent variable, namely the use of e-filing, while the independent variables are usefulness, convenience, security, user satisfaction, and information technology readiness. The data used in this study are primary data using a questionnaire. Respondents are individual taxpayers in police officers who report tax returns using e-filing with puposive sampling or authoritative sampling methods. The population in this study were police taxpayers. The sample used in this study was 150 respondents. Descriptive statistical test, validity test, reliability test, normality test, heteroscedasticity test, multicolinerity test, determination coefficient test, f statistical test, t statistical test, hypothesis testing used in this study is multiple linear regression analysis. The results of this study indicate that: 1) Benefit has a positive effect on the use of e-filing 2) Ease has a positive effect on the use of e-filing 3) Security has a positive effect on the use of e-filing 4) User satisfaction has a positive effect on the use of e-filing 5) Readiness of technology and information has no effect on the use of e-filing. Keywords : E-Filing, Usefulness, Convenience, Security, User Satisfaction, Technology And Information Readiness.